2019
DOI: 10.1364/ol.44.002558
|View full text |Cite
|
Sign up to set email alerts
|

Set of 4d–3 observables to determine any pure qudit state

Abstract: We present a tomographic method which requires only 4d − 3 measurement outcomes to reconstruct any pure quantum state of arbitrary dimension d. Using the proposed scheme we have experimentally reconstructed a large number of pure states of dimension d = 7, obtaining a mean fidelity of 0.94. Moreover, we performed numerical simulations of the reconstruction process, verifying the feasibility of the method for higher dimensions. In addition, the a priori assumption of purity can be certified within the same set … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Then, for each observable A i , the expectation value in the target state, a ρ i = Tr(ρA i ), is approximated by the relative frequency f i = n i /N , experimentally obtained, where n i is the number of trials that resulted in a click of the detectors. In agreement with typical experimental setups based on optical platforms [38,39], we have assumed a source consisting of a pulsed attenuated laser, that emits weak coherent states at the single-photon level. In this context, it is reasonable to assume that the statistics of the photon emission process and the dark counts, caused by self triggering effects in the photon detectors, are Poissonian.…”
Section: Reliability In the Presence Of Noisementioning
confidence: 99%
“…Then, for each observable A i , the expectation value in the target state, a ρ i = Tr(ρA i ), is approximated by the relative frequency f i = n i /N , experimentally obtained, where n i is the number of trials that resulted in a click of the detectors. In agreement with typical experimental setups based on optical platforms [38,39], we have assumed a source consisting of a pulsed attenuated laser, that emits weak coherent states at the single-photon level. In this context, it is reasonable to assume that the statistics of the photon emission process and the dark counts, caused by self triggering effects in the photon detectors, are Poissonian.…”
Section: Reliability In the Presence Of Noisementioning
confidence: 99%
“…For example, if some information about the state is known a priori, a reduction in the number of measurements is feasible. In fact, several works have demonstrated that pure quantum states can be accurately reconstructed from a number of measurements that scales as ∼ d [17][18][19]. Although, in general, an arbitrary quantum system will be in a mixed state, the reconstruction of pure states is especially important since most current applications of quantum information are based on pure states.…”
Section: Introductionmentioning
confidence: 99%
“…In the face of increasing complexity of tomography with the state-space dimension [3], recent effort has been directed to simplify the process using prior information [4,5]. In particular, for a quantum state known to be pure, a number of tomographic techniques has been developed showing that up to five measurement bases will determine it in any finite dimension [6][7][8][9][10]. Although, in practice, purity is just an approximation, in many scenarios it is good enough.…”
mentioning
confidence: 99%
“…Comparing with other tomographic approaches for pure states, which require projective measurements in a fixed number of bases [6][7][8][9][10], the ptychographic technique [11] resorts to a flexible number (n) of projective measurements in a single basis. It also uses simpler settings in the experimental setup, since the rank-r projectors are usually easy to implement.…”
mentioning
confidence: 99%
See 1 more Smart Citation